Relationship between Culturally Responsive Teaching and Student Academic Success in Ghana - Malik, Abdul (American Journal of Education and Practice, 2025)
Purpose: The purpose of this article was to analyze relationship between culturally responsive teaching and student academic success in Ghana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Culturally Responsive Teaching (CRT) in Ghana enhances student success by integrating local languages, traditions, and experiences, improving engagement and performance. It fosters a sense of belonging, reducing dropout rates, but faces challenges like limited teacher training and rigid curricula. Strengthening CRT can bridge learning gaps and promote equity. Unique Contribution to Theory, Practice and Policy: Sociocultural theory, culturally relevant pedagogy (CRP) theory & funds of knowledge theory may be used to anchor future studies on the relationship between culturally responsive teaching and student academic success in Ghana. To ensure effective implementation of CRT, teacher training programs must integrate comprehensive courses on culturally responsive pedagogy. For CRT to be fully embedded into education systems, policymakers must mandate its implementation through education policy reforms.